Assessing empathy in adults: A Malay language validation and measurement invariance of the Empathy Quotient (M-EQ) - Su Woan Wo; Ria Heryani Mumfahir; Cher Yi Tan; Louise Phillips; Min Hooi Yong (PLoS ONE, 2026)
The Empathy Quotient (EQ) is one of the most frequently used scales to measure empathy in adults and has been translated into many languages. However, there is still much debate on its dimensionality from its initial inception. Further, we know very little regarding EQ’s measurement invariance to ensure that the instrument EQ measures the same construct consistently across different groups (e.g., gender, language type) and having meaningful comparisons without bias. In this study, we validated a Malay version of the Empathy Quotient (M-EQ), a self-report questionnaire among Malaysian adults and examined its measurement invariance across gender and language type. We recruited 586 participants aged between 18–53 years ( M age = 23.98, SD = 5.89) to complete the M-EQ. Our confirmatory factor analysis results showed that the M-EQ had two factors (emotional empathy, cognitive empathy) with 23 items retained. The internal consistency and test-retest reliability of the M-EQ was acceptable. Measurement invariance testing indicated that the two‑factor structure was broadly comparable across gender and language groups, with configural and metric invariance supported, although some indices suggested cautious interpretation. Compared to males, females scored higher than males on total M-EQ and both subscales. Taken together, the findings support a psychometrically sound 23‑item version of the EQ in Malay-speaking adults with evidence for internal structural validity, which may be useful for research and applied contexts where brief and culturally appropriate measures of empathy are required. Overall, our findings contribute to ongoing debates on the dimensionality of the EQ, with more research needed to establish convergent and criterion‑related validity of the M‑EQ.